Evaluation Of Internal Control System Using COSO Framework (Case study: Koperasi Nirwana Arta Mandiri) - Aggry Saputra; Zulfachmi Fachmi; Yanu Prapto Sudarmojo (International Journal of Engineering and Emerging Technology, 2017)
Good business activities undertaken by businesses verification and triangulation. Koperasi Nirwana Arta Mandiri has implemented some internal controls but seen from other components such as the control environment and risk assessment is still inadequate and require improvements to improve the effectiveness of the internal control itself.